The jaguar's jewel - Roy, Ron, 1940-; Gurney, John (New York : Random House, 2000)
Dink and his friends use their detective skills to locate a giant emerald missing from a statue delivered to Uncle Warren's museum in New York City
"A Stepping Stone book."
"Grades 2-4"--Cover p. [4]
Keywords: Mystery and detective stories; New York (N.Y.) -- Fiction